PERKEMBANGAN TEKNOLOGI DI HINDIA BELANDA MELALUI MEDIA IKLAN KORAN BINTANG BORNEO BULAN JANUARI-MARET 1929 - Sari, Desti Eka; Rizal Izmi Kusumawijaya; Azmi, Muhammad (History Education Department, Universitas Mulawarman, 2023)
Technology is any means used to facilitate human life in maintaining survival. Technological development is also considered an indicator of the progress of human civilization during its time and is the basis for future technological change and development. The research method used is the historical method, namely the process of examining and analyzing records and relics of the past chronologically and critically through heuristic, critical, interpretative and historiographic activities. Technological developments in the Dutch East Indies (Indonesia) began during the Dutch colonial period and were promoted or advertised through newspapers, one of which was the Bintang Borneo newspaper and technology had a good impact on the people of the Dutch East Indies (Indonesia) in 1929.